Agility development in youth soccer: the efficacy of fixed-role small-sided games - Neag, Ioan; Mihaila, Ion; Fleancu, Leonard Julien; Stancu, Maura; Potop, Vladimir; Barbu, Dumitru; Păun, Laurian – Ioan; Mihai, Ilie (Frontiers in Sports and Active Living, 2025)
PurposeThis study aimed to evaluate the impact of Fixed-Role Small-Sided Games (FRSSGs) on youth soccer players' agility and its components: reaction time, linear speed, and change-of-direction speed (CODS).MethodsThirty-one male U-12 regional soccer players were randomly assigned to the FRSSG group (n = 16; age: 10.63 ± 0.48 years) or the control group (CON) (n = 15; age: 10.89 ± 0.31 years). The intervention program lasted 18 weeks. Pre- and post-intervention tests assessed reaction time, linear sprint speed (10 m and 20 m), CODS (505 and zig-zag tests with/without the ball), and agility (Y-shaped with/without the ball and multiple-signal tests). Statistical analysis included paired t-tests, repeated measures ANOVA, and effect sizes (Cohen's d).ResultsSignificant baseline differences were observed between groups in 10-meter linear speed, and zigzag test performance (p < .05). Within-group improvements were observed for the FRSSG group in the 505 Test (−6.85%, p < .001, d = 1.375), Zigzag Test (−10.77%, p < .001, d = 2.148), CODS Zigzag Ball Test (−9.42%, p < .001, d = 1.434), Y-shape Ball Test (−9.49%, p < 0.001, d = 2.195), and Agility Multi-signal Test (−8.42%, p = .002, d = 0.821). Significant between-group differences favoring FRSSG were found for the 505 Test (p = 0.005, η2 = 0.038), Zigzag Test (p < .001, η2 = 0.435), CODS Zigzag Ball Test (p = 0.004, η2 = 0.04), and Y-shape Ball Test (p = 0.006, η2 = 0.027).ConclusionFRSSGs have been shown to effectively enhance agility and change of direction speed, both with and without the ball, in youth soccer players.